EFFECTIVENESS OF LIGHT GUIDED PANEL TO INCREASE DAYLIGHTING IN BUILDING - Vidiyanti, Christy
Buildings in big cities in Indonesia generally are multi storey and thick masses therefore have limitations in utilizing natural lighting due to the deepness and seperation of the space. The usage of light guided panel (LGP) on the wall of a building, will increase the quality and quantity of space lighting where it is able to reflect and refract the sun's direct light into the deep space. Design of LGP must incorporate several variables, such as latitude and altitude and dailymonthly movement of the sun. The LGP is a lighting openings that in this case is located on the east and west walls of the building. It is designed to be able to accommodate the sunlight with vertical shadow angel (VSA) of 300 up to 850. This LGP is composed from three main components, namely; light reflectors, prismatics light guiding, and shading panels. This study discusses two LGP concepts of 'maximum range’ and 'efficiency of mass’. Through a number of numerical simulations and laboratory testing, are found that LGP is able to provide a better level of illumination for the activities sucah as walking by 20 lux up to room depth of 30 m in March (HSA = 00) and provide a level of illumination of 100 lux up to room depth of 13 m when using the concept of ‘maximum range' and up to 15 m when using the concept of 'efficiency mass panel'. The usage of LGP in buildings can improve the quality of indoor lighting that the room has a more uniform lighting levels by 48% -61% and increase the stability of the lighting levels by 4% -37% better than the light openings without LGP. The LGP has the potentials to be applied on thick buildings without partition space, such as double-loaded corridors, large factory buildings, stations, airports, terminals, multipurpose buildings, offices, public lecture halls, laboratories, sports hall, parking buildings, etc.